Sustainability of Home Garden Program in Batu City - Wara' Geffa Az Zahra; Fitria Dina Riana; Sujarwo (Institut Pertanian Bogor, 2026)
The home garden program, also known as KRPL (Kawasan Rumah Pangan Lestari) or P2L (Pekarangan Pangan Lestari), has the potential to boost food security and community welfare in Batu City, East Java Province. This study used a multidimensional approach to assess the program's sustainability, considering social, environmental, and economic elements. The Multidimensional Scaling (MDS) method was employed in the study as part of the Rapid Appraisal for Home Garden (RAP-HG) approach. The data was processed using Microsoft Excel software, yielded three key results: sustainability index ordination analysis, Monte Carlo analysis, and leverage analysis. The findings revealed that the social dimension had the highest sustainability index (63.06%), followed by the environmental dimension (59.94%) and the economic dimension (59.80%). Overall, the program's sustainability is rated moderately sustainable. This finding suggests that, while the program has had a positive influence on sustainability, further improvements are required to achieve the highest level, which is highly sustainable. The approach was then developed using a leverage analysis to provide valuable insights for policymakers and program implementers as they construct more sustainable initiatives to improve local food security. Keywords: Batu City, food security, home garden, RAP-HG, sustainability